2022
DOI: 10.1097/dss.0000000000003398
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of CT-Based Conformal Electron Beam Radiation Therapy After Keloid Excision

Abstract: BACKGROUND Adjuvant computed tomography-based conformal electron beam radiation therapy (RT) for patients with keloids enables radiation oncologists to customize the target volume with precision and deliver the maximal prescription dose while sparing normal surrounding tissues. OBJECTIVE To report treatment and cosmetic outcomes by the patient's self-assessment survey. METHODS Medical records of patients with keloids, who were treated with postoperative electron beam RT between January 2015 and December 2020, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Although some studies have shown that the recurrence rate of postoperative electron beam treatment of keloids is not significantly different from that of x-ray treatment ( 9 , 66 ). However, the energy is delivered to a depth of 2–5 cm by the accelerator to keloids, and electron beam radiotherapy is more suitable than x-ray therapy for flat and lumpy keloids ( 67 ). Compared with X-ray, the more concentrated radiation coverage is more suitable for treating localized superficial lesions such as keloids without causing serious damage to deeper tissues while treating them.…”
Section: Electron Beammentioning
confidence: 99%
“…Although some studies have shown that the recurrence rate of postoperative electron beam treatment of keloids is not significantly different from that of x-ray treatment ( 9 , 66 ). However, the energy is delivered to a depth of 2–5 cm by the accelerator to keloids, and electron beam radiotherapy is more suitable than x-ray therapy for flat and lumpy keloids ( 67 ). Compared with X-ray, the more concentrated radiation coverage is more suitable for treating localized superficial lesions such as keloids without causing serious damage to deeper tissues while treating them.…”
Section: Electron Beammentioning
confidence: 99%